(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Objective: Skeletal scintigraphy is highly sensitive and widely used for the detection of metastatic disease especially in breast cancer. The study was aimed to evaluate the pattern of skeletal metastasis in breast cancer patients with whole body bone scan using 99mTechnetium -Methyl Diphosphonate (99mTc-MDP) to aid proper diagnosis, staging, management and prognosis. Study design: Single center based retrospective study. Patients and methods: The study was conducted among the histopathologically proven breast cancer patients referred to INMAS, Barishal for 99mTc-MDP bone scintigraphy between March 2016 and March 2017. Bone scan was done with SPECT digital dual head gamma camera (Siemens S series) 3 hours after intravenous bolus injection of 20 mCi 99m Tc-MDP. Results: Out of total 96 patients, 47(49%) were found positive for skeletal metastases and among them 31(66%) had only axial skeletal metastases. Appendicular skeletal metastases were seen in 5 (11%) patients. Both axial and appendicular skeletal metastases were found in 11(23%) patients. Conclusion: For equivocal lesions SPECT is better than planar scintigraphy alone to characterize and comment confidently. Metastatic lesions detected by bone scintigraphy in breast cancer patients keep a significant impact on patient management. Bangladesh J. Nuclear Med. 23(1&2): 37-39, 2020